The COVID-19 Lockdown and Players’ Match Statistics in Serie A - Metelski, Adam (Quality in Sport, 2021)
Purpose: In March 2020, most sports competitions around the world were suspended, ended, or canceled. As a result of the COVID-19 lockdown, citizens and athletes from many countries had to stay at home. It was a very unusual break for athletes and it caused a lot of discussion how it could affect the performance of professional players. This study aims to check how the lockdown due to COVID-19 affected the players’ match statistics in the premier Italian football league – Serie A. The Italian league was chosen deliberately because this country was particularly hard hit by the onset of the COVID-19 pandemic. Design/methodology/approach: Five-fixture rounds played after the restart (since 20th June 2020) of the 2019/2020 season were analyzed and compared with the five-fixture rounds immediately preceding the lockdown (played in February and March). In this way, it was possible to check whether the break in the games and training had significant impact in the initial period after return to play. Findings: The results indicate that the players, in general, managed to stay in good overall shape during the lockdown, but when competition resumed, they attempted much fewer dribbles and tackles. Research and practical limitations/implications: The research focuses on the Italian league. The influence of Covid-19 on sport and society varied from country to country. As a result, lockdown in particular regions could have had different impacts. Originality/value: The value of the study is a description of the significance of a not-expected break in competition and training for the statistics of football players and thus the quality of football games.